An ameloblastoma associated with cardiofaciocutaneous syndrome. (2nd June 2017) - Toole, J.; Napier, S.; Marley, J.
Abstract: This case describes the management of a plexiform unicystic ameloblastoma in a child with cardiofaciocutaneous syndrome. This was managed conservatively, which has allowed the patient to undergo normal dental development. There are no signs of recurrence 4 years post‐operatively and the use of magnetic resonance imaging in monitoring has ensured the patient's exposure to ionising radiation is minimised. The patient's cardiofaciocutaneous syndrome was linked to a BRAF mutation. This gene is involved in cell proliferation and has recently been shown to have a link with mandibular ameloblastomas. As far as the authors are aware, this is the published first case of an ameloblastoma in a patient with cardiofaciocutaneous syndrome.